Repeated Game for Distributed Estimation in Autonomous Clustered Wireless Sensor Networks. (22nd October 2015) - Liu, Guiyun; Liu, Yonggui; Yao, Jing; Chen, Hongbin; Tang, Dong
Abstract : A commonly encountered problem in wireless sensor networks (WSNs) applications is to reconstruct the state of nature, that is, distributed estimation of a parameter of interest through WSNs' observations. However, the distributed estimation in autonomous clustered WSNs faces a vital problem of sensors' selfishness. Each sensor autonomously decides whether or not to transmit its observations to the fusion center (FC) and not be controlled by the fusion center (FC) any more. Thus, to encourage cooperation within selfish sensors, infinitely and finitely repeated games are firstly modeled to depict sensors' behaviors. Then, the existences of Nash equilibriums for infinitely and finitely repeated games are discussed. Finally, simulation results show that the proposed Nash equilibrium strategies are effective.